Management of oesophageal foreign bodies in pediatric patients: our experience - Mandal, Manit M.; Panchal, Ajay J.; Kumar, Rakesh; Kapadia, Parth B.; Valiya, Vipul; Shah, Vidhi; Kher, Shanu (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Amongst pediatric patients, oesophageal foreign bodies (OFBs) are relatively common clinical problem. Majority pass harmlessly through gastrointestinal tract, some can cause complications or morbidities. Our study considered and reviewed our experience in managing OFBs in pediatric patients, with emphasis on the management and outcomes of complicated cases. Methods: 77 cases of OFBs (diagnosis established), upto 12 years of age admitted at our tertiary hospital between January 2015 to December 2020 (duration of 6 years) were reviewed and analysed. On the basis of our analysis accounting demographic data, presenting symptoms, workup investigation, management, complications and outcomes, results and conclusions were derived. Results: Amongst cases, 43 were male and 34 female. Mean age for our cases was 5.4 years. 56 cases (72.7%) cases presented in the hospital within first 24 hours. Commonest foreign body found in 64 cases (83.1%) was coin. Most cases had history of witnessed ingestion. Commonest presentation was asymptomatic (with history of witnessed ingestion), followed by complaint of vomiting and drooling of saliva. Most patients were discharged within 48 hours post-operatively except for 2 patients who presented intra-operatively with edematous inflamed mucosa with slight charring on oesophagoscopy where foreign body was button battery (cell). Follow-up period ranged from 2 to 8 months and all patients had complete recovery without any sequelae. Conclusions: Our experience of 6 years with 77 pediatric patients with OFBs having various presentations have been reviewed, analysed and concluded here. All the patients had complete recovery without any sequelae.